Correction: The Dkk3 gene encodes a vital intracellular regulator of cell proliferation. - Jack L Leonard; Deborah M Leonard; Scot A Wolfe; Jilin Liu; Jaime Rivera; Michelle Yang; Ryan T Leonard; Jacob P S Johnson; Prashant Kumar; Kate L Liebmann; Amanda A Tutto; Zhongming Mou; et al. (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0181724.].